A148: A Multi‐Center, Double‐Blind, Randomized‐Withdrawal Trial of Subcutaneous Golimumab in Pediatric Patients With Active Polyarticular Course Juvenile Idiopathic Arthritis Despite Methotrexate Therapy: Week 48 Results. Issue 11 (March 2014) - Brunner, Hermine; Ruperto, N.; Tzaribachev, N.; Horneff, G.; Wouters, C.; Panaviene, V.; Chasnyk, V.; Abud‐Mendoza, C.; Cuttica, R.; Reiff, A.; Maldonado‐Velázquez, M.; Rubio‐Perez, N.; et al.
Abstract : Background/Purpose: To assess efficacy and safety of SC golimumab (GLM) in polyarticular pediatric juvenile idiopathic arthritis pts (aged 2 to <18 yrs) with active arthritis despite MTX for ≥3 months. Methods: In GO‐KIDS, a 3‐part randomized double‐blind, PBO‐controlled, withdrawal trial in pts with active JIA with a polyarticular course (≥5 active joints) and disease duration of ≥6 months despite current MTX (10–30 mg/m 2 /wk). In Part 1(wk 0–12), all pts received open‐label (OL) 30 mg/m 2 GLM SC (max 50 mg) q4 wks with stable MTX dose. At wk 16, pts with ACR JIA 30 response entered Part 2 (wk 16–48). In Part 2, pts were randomized to continue GLM or switch to PBO q4 wks. Upon Part 2 completion at wk 48 or ACR JIA flare in Part 2, pts received OL GLM in Part 3. Primary endpoint was proportion of ACR JIA 30 responders at wk 16 without a JIA flare in Part 2 using wk 16 as baseline measurement. Secondary outcomes were ACR JIA 30/50/70/90 response rates and inactive disease rates at wk 16 and wk 48 by group and safety. Results: 173 pts (Caucasian 87.9%, 75.7% females; age [median/range] 12 yrs/2–17 yrs) with moderately active disease were enrolled (Table 1 ); 19 (11%) were d/c in Part 1 (lack of efficacy n = 14, AE n = 4, withdrawal of consent n = 1). In Part 1, 151 of 173 (87.3%) achieved an ACR JIA 30 response and 36.1% inactive disease status (Table 2 ). There were 154 pts randomized double‐blind in Part 2 (PBO n = 76; continued GLM n = 78). At the end of Part 2, no significant differences between groups in JIA ACR non‐flare rates and trial did not meet primary endpoint [PBO‐grp vs. GLM‐grp: 52.6% vs. 59.0%, p = 0.41) nor were there differences for major secondary endpoints (Table 2). In contrast, sustained response in both groups (PBO, GLM) relative to wk 0 (Table 1 and 2). 6.5% (10 of 154) of pts d/c therapy after wk16 through wk 48. Through wk 48, AEs, serious AE (SAE), and serious infections were reported in 87.9%, 13.3%, and 2.9% of all randomized pts, respectively. Most common SAE was JIA exacerbation. No deaths, active TB or malignancies were reported (1). GLM‐treated pt experienced SAE of toxic hepatitis and 1 had SAE of hepatic enzyme increase. One pt switched from PBO to GLM experienced SAE of serum sickness reaction, resulting in GLM d/c. Proportion of pts with ≥1 injection site reaction was 8.1%. None of the reactions were serious, severe, or led to GLM d/c. Conclusion: JIA pts with active polyarticular dis ease demonstrated rapid response to GLM with 16 wks of OL treatment, resulting in inactive disease in 36% of the pts. The lack of differences in flare rates between GLM and PBO arms from wk 16 to 48 among OL GLM responders needs further evaluation. Safety profile was acceptable and injections well tolerated.